Intraperitoneal access by closed method (veress needle) versus open (Hasson’s) method in laparoscopic surgery to create pneumoperitoneum - Chotai, Neet R.; Choksi, B. B.; Damor, Sushil; Bhedi, Amul (International Surgery Journal, 2017)
Background: Access into the abdomen is the one challenge of laparoscopy that is particular to the insertion of surgical instruments through small incisions. In the last three decades, rapid advances in laparoscopic surgery have made it an invaluable part of general surgery, but there remains no clear consensus as an on optimal method of entry into the peritoneal cavity. The objective of this study was to study the comparison and efficacy between closed (veress needle)and open method (Hasson’s) of intraperitoneal access to create pneumoperitoneum in laparoscopic surgeries. Methods: All patients >18 year undergoing laparoscopic procedure at Sir Sayajirao Gaekwad Hospital attached to Medical College Baroda from November 2015 to November 2016, and include 160 patients. This was Prospective study and total 160 cases of Laparoscopic surgery was taken in 1-year period. Methods used to create pneumoperitoneum were of surgeon’s choice in each case. Cases were performed by one method more than other method (63 patients by veress needle and 97 by open method). Student t test (two tailed, independent) had been used to find the significance of study parameters on continuous scale between two groups. All data were entered in Microsoft Excel sheet. Data calculation was done in software - Microsoft Excel and Medcalc statistical software 16.8.4.0. Results: The Mean operative time for access in veress needle group was 5.12 mins as compare to open method where it was 3.94 mins. Port site Gas leakage was slightly more in open method. There were no any major complications occurred in any group. There were minor complications occur in both methods at access like; omental injury, port site gas leakage, extra-peritoneal insufflations, loss of space and entry in wrong plane. Conclusions: For intraperitoneal access in laparoscopy, both the closed and the open methods are safe and the open technique had a time advantage over the closed method.